Pengembangan Media Pembelajaran Smart Culture Hunter Pada Materi Indonesiaku Kaya Budaya Kelas IV SDN 01 Belik Pemalang - Dinda Apriliani; Pamujo Pamujo (Journal on Education, 2024)
Learning media is used as a way to convey messages to students so that they can be conveyed more clearly and achieve educational goals, the current modern era requires digital-based learning media so that it can keep up with the times. Seeing this, researchers are interested in developing Smart Culture Hunter digital media after obtaining information that Class IV students of SDN 01 Belik have difficulty visualizing the material, especially on the material My Indonesia is Rich in Culture because of the extensive material and limited time so that students have difficulty describing the diversity of Indonesia. The purpose of the researcher developing Smart Culture Hunter is to overcome this problem, this learning media can be used anywhere so that learning becomes more flexible. This research uses the ADDIE model and involves various data collection instruments, including validation surveys from media and material experts, practicality questionnaires from teachers and students, and pre-test and post-test questions. The results of the research on Smart Culture Hunter media show that: Media expert validation resulted in a very valid score of 94%, material expert validation resulted in a very valid score of 96% and linguist validation resulted in a score of 95%. The teacher response questionnaire showed 100% and the student response questionnaire showed a result of 88% stating that Smart Culture Hunter was very practical. The N-Gain score was 0.5 from the pre-test and post-test, meeting the effectiveness requirements.